Formulasi Granul Sarang Walet Putih (Aerodramus fuciphagus) dengan Variasi Kombinasi Maltodextrin dan Povidon - Suena, Ni Made Dharma Shantini; Adrianta, Ketut Agus; Wardani, I Gusti Agung Ayu Kusuma; Antari, Ni Putu Udayana (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
Abstract: White swallow nest (SWP) contains Epidermal Growth Factor, which can increase immunity, and glutathione, which functions as an antioxidant. SWP has a high potential to become an antioxidant-rich immunomodulatory drink. Combining maltodextrin and povidone in a granule formula can protect the active substance from heat and maintain the flavor components. However, the wrong concentration can reduce the quality of the resulting granules. This study aims to obtain a combination of maltodextrin and povidone concentrations in SWP granule formulations that produce granules with the best quality and physical stability. The wet granulation method prepared the ten SWP formulas with combined concentrations of maltodextrin-povidone (code: F1 to F10). Evaluation of the physical quality of the granules (organoleptic, pH, soluble time, moisture content, compressibility index, and flow properties) was evaluated on the first, seventh, fourteenth, and twenty-first days. Linear regression is used to create an equation model of the effect of formulation on granule quality parameters. Formula F6 has the lowest compressibility index and the highest flow rate. There was no significant difference for all physical quality parameters of all formulas during storage (p>0.05). The effect of varying concentrations of maltodextrin is inversely proportional to the effect of varying concentrations of povidone on the physical quality of SWP granules. From the research results, it can be concluded that the combination of maltodextrin (5%) and povidone (1%) in F6 produces granules with the best physical quality. All formulas are stable during storage.